Meningkatkan Hasil Belajar IPS Melalui Penerapan Model Pembelajaran Kooperatif Tipe Snowball Throwing pada Kelas IV SDN 98 Tongko - D, Hamsah (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
This study aims to improve the learning outcomes of fourth-grade students of SDN 98 Tongko in Social Studies through the Snowball Throwing Cooperative Learning Model. This study is a classroom action research (CAR) conducted in 2 cycles. The subjects of the study were 20 fourth-grade students of SDN 98 Tongko. Data obtained based on observations and student learning outcomes based on test results per cycle were analyzed quantitatively and qualitatively. The results showed that classically in cycle I, 13 students out of 20 students obtained a score of ≥75 with a percentage of completion of 65%. In cycle II, the learning outcomes obtained showed an increase, where classically, students who obtained a score of ≥75 increased to 18 students out of 20 students with a percentage of completion of 90%. Based on these results, it can be concluded that the learning outcomes of students in fourth-grade students of SDN 98 Tongko in Social Studies increased through the application of the Snowball Throwing Cooperative Learning Model.